Challenges experienced by students studying medicine through English medium instruction - Alanazi, Khatmah; Curle, Samantha (Frontiers in Education, 2024)
English is increasingly being used as a medium of instruction (MoI) in many institutions for teaching academic subjects, such as physical science and medical subjects. Although research evidence is emerging to support the positive effects English Medium Instruction (EMI) has on student learning, such as preparing students for professional careers and improving English language proficiency, students also face challenges when studying through EMI, particularly linguistic-related challenges. This study aims to investigate the challenges that medical students encounter when learning medicine through EMI in medical education programmes in Saudi Arabia. A mixed-method research approach was adopted. A questionnaire was distributed to 373 students studying at four different medical schools, and follow-up semi-structured interviews were conducted with 60 students. The findings revealed that students encountered numerous challenges when studying medicine through EMI including reading medical-related teaching materials, understanding lectures taught purely in English, and being able to speak fluently. Notably, these challenges were more salient in the students’ first or second years of their university studies, however dissipated as students progressed in their studies. Pedagogical implications of these findings are discussed.